Taxonomic clarification of two Nearctic Strumigenys (Hymenoptera: Formicidae) - Booher, Douglas B. (Zootaxa, 2019)
In 1901, Forel described an ant species from a relatively poorly known genus of ants from North America, naming it Strumigenys pilinasis. In 1931 M. R. Smith obtained the holotype and redescribed it, and he included a first illustration. The description was incomplete and the illustration resembled Strumigenys brevisetosa Smith, 1935, more than it resembled S. pilinasis, which led subsequent taxonomists to make consistent misidentifications and to consider S. brevisetosa to be a synonym of S. pilinasis. Here I redescribe both S. pilinasis and S. brevisetosa (revived status). Strumigenys manni Wesson & Wesson, 1939, and S. ohioensis Kennedy & Schramm, 1933, are new junior synonyms of S. pilinasis, and S medialis Kennedy & Schramm, 1933, is a new junior synonym of S. brevisetosa.